Synthesis and Optical Properties of Gamma-Alumina Nanoparticles and its Antibacterial Properties - Merat karimi; Ehsan Sadeghi; Mostafa Zahedifar (Fasa University of Medical Sciences, 2020)
Background & Objective: By increasing resistance due to overuse of antibiotics, it seems necessary to find alternative materials that have both antibacterial properties close to antibiotics and have minimal side effects for humans. Abundant research has been done on the use of nanoparticles with antibacterial properties. The aim of this study is to investigate the antibacterial properties of gamma alumina quantum dots. Materials & Methods: Gamma alumina quantum dots (Al2O3-g) were prepared by sol-gel method. Structural, physical and optical properties and of this nanoparticles were appraised by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), photoluminescence spectroscopy (PL), visible-ultraviolet spectroscopy (UV-Vis) and Fourier transform infrared (FTIR) spectroscopy. Biological activity of gamma alumina nanoparticles against 11 types of bacteria was measured by MIC and MBC methods. Results: Results show the size of the synthesized nanoparticles is less than ten nanometers. The power of minimal bactericidal concentration (MBC) and minimal inhibitory concentration (MIC) by gamma alumina quantum dots is related to its particle size, which interpenetrates and destroys the bacterial wall more easily. Gamma alumina quantum dots show good activity against bacterial growth. Conclusion: The antibacterial activity of alumina quantum nanoparticles showed desirable effects for a variety of gram-positive and gram-negative bacteria, fungi and yeasts at the lowest inhibitory concentrations. These nanoparticles can be a great alternative to antibiotics and making these nanoparticles is economical, cost-effective and is less time-consuming.